Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
(разб.) + KOH = H2O + KNO3
Полнаяформа:
K+ + OH− + H+ + NO3− = K+ + NO3− + H2O
Краткаяформа:
OH− + H+ = H2O
HNO3 + KOH = H2O + KNO3
Полнаяформа:
K+ + OH− + H+ + NO3− = K+ + NO3− + H2O
Краткаяформа:
OH− + H+ = H2O
HNO3(разб.) + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
HNO3 + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
HNO3(разб.) + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
HNO3 + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
HNO3(разб.) + KOH = H2O + KNO
Полнаяформа:
K+ + OH− + H+ + NO3− = K+ + NO3− + H2O
Краткаяформа:
OH− + H+ = H2O
Химаша | решаю реакции по химии, [28.12.2020, 22:40]
HNO3 + KOH = H2O
Полнаяформа:
K+ + OH− + H+ + NO3− = K+ + NO3− + H2O
Краткаяформа:
OH− + H+ = H20
HNO3(разб.) + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
HNO3 + KOH = H2O + KNO3
Полнаяформа:K+ + OH- + H+ + NO3- = K+ + NO3- + H2O
Краткаяформа:OH- + H+ = H2O
2) перекрывает доступ кислорода.